Research approaches for evaluating opioid sparing in clinical trials of acute and chronic pain treatments: Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials recommendations. Issue 11 (8th November 2021) - Gewandter, Jennifer S.; Smith, Shannon M.; Dworkin, Robert H.; Turk, Dennis C.; Gan, Tong J.; Gilron, Ian; Hertz, Sharon; Katz, Nathaniel P.; Markman, John D.; Raja, Srinivasa N.; Rowbotham, Michael C.; Stacey, Brett R.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Randomized clinical trials have demonstrated the efficacy of opioid analgesics for the treatment of acute and chronic pain conditions, and for some patients, these medications may be the only effective treatment available. Unfortunately, opioid analgesics are also associated with major risks (eg, opioid use disorder) and adverse outcomes (eg, respiratory depression and falls). The risks and adverse outcomes associated with opioid analgesics have prompted efforts to reduce their use in the treatment of both acute and chronic pain. This article presents Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT) consensus recommendations for the design of opioid-sparing clinical trials. The recommendations presented in this article are based on the following definition of an opioid-sparing intervention: any intervention that (1) prevents the initiation of treatment with opioid analgesics, (2) decreases the duration of such treatment, (3) reduces the total dosages of opioids that are prescribed for or used by patients, or (4) reduces opioid-related adverse outcomes (without increasing opioid dosages), all without causing an unacceptable increase in pain. These recommendations are based on the results of a background review, presentations and discussions at an IMMPACT consensus meeting, and iterative drafts of this article modified to accommodate input from the co-authors. We discuss opioid sparing definitions, study objectives, outcome measures, the assessment of opioid-related adverse events, incorporation of adequate pain control in trial design, interpretation of research findings, and future research priorities to inform opioid-sparing trial methods. The considerations and recommendations presented in this article are meant to help guide the design, conduct, analysis, and interpretation of future trials.